Optimal visualization of the fetal four‐chamber and outflow tract views with transabdominal ultrasound in the morbidly obese: Are we there yet?. Issue 9 (30th September 2015) - Adekola, Henry; Soto, Eleazar; Dai, Jing; Lam‐Rachlin, Jennifer; Gill, Navleen; Leon‐Peters, Jocelyn; Puder, Karoline; Abramowicz, Jacques S.
ABSTRACT Background To compare optimal visualization of the four‐chamber and outflow‐tract views of the fetal heart on sonographic examination between morbidly obese (body mass index [BMI] ≥ 40 kg/m2) and nonobese (BMI < 25 kg/m2) pregnant women. Methods In this retrospective cohort study, we included records and images from 509 pregnant women who had first undergone sonographic examination between 18 and 36 weeks' fetal gestational age. Results Compared with the nonobese women, morbidly obese women had lower optimal visualization of the four‐chamber and outflow‐tract heart views: four‐chamber view, morbidly obese, 83/186 (44.6%), versus nonobese, 283/323 (87.6%), and outflow‐tract view, morbidly obese, 80/186 (43%) versus nonobese, 258/290 (89%); p < 0.0001 for each comparison. Similar outcomes were observed when the results from each subcategory of morbidly obese women (ie, BMI 40–49.9, 50–59.9, and ≥60 kg/m2) were compared with that from nonobese women; p < 0.0001 for each comparison. These outcomes remained the same regardless of whether this comparison was made among those who had their examination before or at 19 weeks' or more gestational age. Among the morbidly obese women, there was no difference in optimal visualization of the four‐chamber or outflow‐tract views regardless of whether the examination was performed at <23 weeks' or at ≥23 weeks' gestational age: four‐chamber view <23 weeks, 44.8% (78/174), versus four‐chamber view ≥23 weeks, 41.7% (5/12); p = 0.8, and outflow‐tract view <23 weeks, 43.1% (75/174), versus outflow‐tract view ≥23 weeks, 41.7% (5/12); p = 0.9. After controlling for maternal age and race, the odds of visualizing the four‐chamber and outflow‐tract views in the morbidly obese were reduced compared with those in their nonobese counterparts: odds ratio (OR) for four‐chamber, 0.13; 95% confidence interval (CI), 0.08–0.21, and OR for outflow‐tract, 0.11; 95% CI, 0.07–0.17. Conclusions Optimal visualization of the fetal four‐chamber and outflow‐tract views was achieved in less than 50% of morbidly obese women, compared with almost 90% in nonobese women. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound43:548–555, 2015